Comparison of chewing ability, oral health-related quality of life, and nutritional status before and after the insertion of complete denture among edentulous patients in Lucknow - Punit Karmacharya; Sabyasachi Saha; Minti Kumari (Wolters Kluwer Medknow Publications, 2017)
Introduction: Reduction in chewing ability is one of the most impactful sequels resulting from oral disorders and is a common problem reported among elderly adults. This tends to make them more irritable and to lose interest in life. One of the major problems among the old age people is loss of teeth, affecting their chewing ability, dietary intake, and overall general health. Aim: To assess and compare the chewing ability, oral health-related quality of life (OHRQoL), and nutritional status before and after insertion of complete denture among elderly edentulous patients attending the Dental Hospital, Lucknow. Materials and Methods: An intervention study design was used and nonprobability convenience sampling method was used. The population under the study consisted of edentulous patients, both males and females aged 50 years and above. A predesigned questionnaire was used to collect the data that include sociodemographic information and oral hygiene practices. Clinical examination was done using Geriatric Oral Health Assessment Index (GOHAI), Mini Nutritional Assessment, and body mass index. Comparisons between pre- and post-insertion of denture were evaluated at three levels, at baseline and 1st and 3rd month. Results: Chewing ability, GOHAI, and data from food intake questionnaire showed statistically significant improvement from baseline to 3rd month, but calf circumference had no statistically significant improvement. Conclusion: The denture insertion was effective in increasing the chewing ability, food intake, and OHRQoL in the elderly.